The method of analysis of the financial condition of the commercial organization - Y. Karpenko; N. Malykh; R. Chvanov (Вестник университета)
In the article the method of analysis of the financial condition of the commercial organization. The theoretical material is reinforced by practical calculations. The authors emphasize that a permanent and systematic analysis of the financial condition allows the organization to remain competitive and increase its potential in business cooperation. Furthermore, on the basis of financial analysis results it can be concluded that the extent to which the economic interests are guaranteed organization and its business partners.